An Algorithm Based on the Backtracking Method for Cropping-Systems and the Rotation of Cultures. (2016) - Popescu, Doru Anastasiu; Bold, Nicolae; Bold, Alina Claudia
Abstract: Cropping-system is an old agricultural method which has benefits over both the soil and the crop. Generating a cropping-system is a slightly difficult task, which can put the unexperienced and even trained farmers in difficulty. The rules that must be respected are numerous and are particular to every plant and the content in nutritive substances of the soil. Therefore, the technology can help the farmer to make a decision within the management system of the farm. The backtracking method is helpful in this situation for generating all the possibilities of a cropping-system, respecting the rules presented in this type of system. In this paper we present a method of generating them and calculating the most profitable cropping-system possibility, based on a backtracking algorithm and also a Java GUI for an easier overview on the issue and on the results.